2009
DOI: 10.3844/ajidsp.2009.106.108
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bleeding Time and Clotting Time in Different Blood Groups

Abstract: Problem statement:Researchers have demonstrated that epistaxis is more often encountered in patients having blood group O probably due to lower expression of von Willebrand factor. We had taken up this study to find out if there is any definite relationship between the blood groups with the bleeding time and clotting time in our population. Approach: This retrospective study was conducted in the department of physiology in our institution. The available detail reports of 740 students passing through 1st year o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 8 publications
(8 reference statements)
4
14
1
Order By: Relevance
“…This means that the clotting time and the bleeding time will be elevated among the O group individuals compared to the other groups. But, as per the study done by Mahapatra et al (15), clotting time was prolonged in the group Bindividuals and bleeding time was prolonged in the AB group compared to other groups. Out study also proved the same findings where the bleeding time was comparatively increased among the B group and the clotting time was increased in the individuals among AB group.…”
Section: Discussionmentioning
confidence: 48%
“…This means that the clotting time and the bleeding time will be elevated among the O group individuals compared to the other groups. But, as per the study done by Mahapatra et al (15), clotting time was prolonged in the group Bindividuals and bleeding time was prolonged in the AB group compared to other groups. Out study also proved the same findings where the bleeding time was comparatively increased among the B group and the clotting time was increased in the individuals among AB group.…”
Section: Discussionmentioning
confidence: 48%
“…Evaluation of blood groups, bleeding time and clotting time are the most important and initial haematological parameters. In a study by B Mahapatra et al (4) O group was found in more number of students (37.8%) than A (21.9%), B (34%) and AB (6.3%). In another study by Roy B et al, (1) O blood group was also the more prevalent group (35.2%) than A (30.5%), B (28.9%) and AB (5.5%).…”
Section: Discussionmentioning
confidence: 86%
“…This was in contrast to the study performed by Mahapatra B et al where BT was more in B blood group. (4) In another study by Baishya R et al, BT was most prolonged in O group. (5) Aleem A et al found Bleeding time to be greater than others in AB blood group in females and 'O' blood group in males but the values were not significantly different.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations